[tex]\displaystyle E1) \\
a) \\
3+x+2i =4+(7+5y)i \\
3+x=4~~ \Longrightarrow ~~ x=4-3=\boxed{1} \\
7+5y=2~~ \Longrightarrow ~~ y= \frac{2-7}{5} =\frac{-5}{5} =\boxed{-1} \\ \\
b) \\
x=\boxed{1} \\
-7=-(4-y) \\
-7 = -4+y \\
y = -7+4 = \boxed{-3}[/tex]
[tex]\displaystyle c) \\
(3x-2y)-(x-7y)i=-1-(y-4)i \\
3x-2y=-1 \\
x-7y=y-4 \\
------- \\
3x-2y=-1 \\
x-8y= -4 ~~~~~~~ \Longrightarrow~~~x=8y-4 \\
------- \\
3(8y-4)-2y=-1 \\
24y-12-2y=-1 \\
22y=11 \\
y= \frac{11}{22} =\boxed{ \frac{1}{2} } \\
x=8y-4 = 8 \times \frac{1}{2} -4=4-4 =\boxed{0}[/tex]
[tex]\displaystyle d) \\
\frac{x}{3}- \frac{y}{2}= \frac{1}{6} \\
-(x-y)=(x+1) \\
--------- \\
2x-3y=1 \\
-2x+y=1 \\
\text{--------------------- adunam fractiile} \\
-2y=2 ~~~\Longrightarrow~~~y= \frac{2}{-2} =\boxed{-1} \\
2x-3 \times (-1) =1 \\
2x-3=1 \\
2x=-2~~~\Longrightarrow~~~x= \frac{-2}{2} =\boxed{-1} [/tex]